Systemic inflammatory indices mediate the association between hyperuricemia and left ventricular hypertrophy: evidence from a single-center retrospective cross-sectional study - Li, Jingyuan; Xu, Yang; Li, Ruting; Huang, Xin; Hu, Shuhui; Yan, Fei; Gong, Ying; Zhang, Xiaoqing; Sun, Fengyao; Chen, Lei; Chen, Ying (Frontiers in Endocrinology, 2026)
AimsHyperuricemia (HUA) is associated with left ventricular hypertrophy (LVH), a reversible marker of cardiac injury. Systemic inflammation drives ventricular remodeling, and the systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI) may reflect this process. This study investigated their associations with LVH in patients with HUA.MethodsWe analyzed 3, 632 patients with HUA hospitalized between 2014 and 2024, excluding those with prior hypertension, diabetes, or advanced chronic kidney disease. Baseline demographic, biochemical, and echocardiographic data were collected. LVH was defined by sex-specific left ventricular mass index thresholds. SII and SIRI were calculated, log-transformed, and analyzed by k-means clustering. Associations with LVH were assessed using logistic regression, restricted cubic spline (RCS), and threshold effect models. Mediation analysis evaluated their role between serum urate and LVH.ResultsAmong all patients, 452 (12.5%) had LVH. Compared with non-LVH patients, those with LVH were older, more often female, and exhibited higher systolic blood pressure, serum urate, glucose, SII, and SIRI, and lower eGFR and LVEF (all p < 0.05). Elevated SII, SIRI, and high inflammatory patterns were independently associated with LVH (all p < 0.01). RCS revealed a nonlinear “J-shaped” association for lnSII with a threshold at 5.99, while lnSIRI showed a linear dose–response. Mediation analysis indicated systemic inflammation partially mediated the urate–LVH relationship (11.9% for lnSII, 29.9% for lnSIRI).ConclusionIn HUA patients, SII and SIRI are positively correlated with LVH and partially mediate the relationship between urate and cardiac remodeling, emphasizing the role of systemic inflammation in hyperuricemia related cardiovascular diseases.